An eco-friendly process to extract hydroxyapatite from sheep bones for regenerative medicine: Structural, morphologic and electrical studies - GÜNDÜZ, OĞUZHAN; OKTAR, FAİK NÜZHET (My University, 2023)
Hydroxyapatite (HA) promotes excellent bone regeneration in bone-tissue engineering, due to its similarity to bone mineral and its ability to connect to living tissues. These factors promote the osteointegration process. This process can be enhanced by the presence of electrical charges, stored in the HA. Furthermore, several ions can be added to the HA structure to promote specific biological responses, such as magnesium ions. The main objective of this work was to extract hydroxyapatite from sheep femur bones and to study their structural and electrical properties by adding different amounts of magnesium oxide. The thermal and structural characterizations were performed using DTA, XRD, density, Raman spectroscopy and FTIR analysis. The morphology was studied using SEM, and the electrical measurements were registered as a function of frequency and temperature. Results show that: (i) an increase of MgO amount indicates that the solubility of MgO is below 5%wt for heat treatments at 600 °C; (ii) the rise of MgO content increases the capacity for electrical charge storage; (iii) sheep hydroxyapatite presents itself as a natural source of hydroxyapatite, environmentally sustainable and low cost, and promising for applications in regenerative medicine.
Keywords: Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Biomedical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, BİYOMATERYAL; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; MATERIALS SCIENCE, BIOMATERIALS; ENGINEERING, BIOMEDICAL; Biyomalzemeler; Fizik Bilimleri; Biyomedikal mühendisliği; Biomaterials; Physical Sciences; biomaterials; bone regeneration; eco-friendly; electrical properties; magnesium oxide; natural hydroxyapatite